Solvent- and phase-controlled photochirogenesis. Enantiodifferentiating photoisomerization of (Z)-cyclooctene sensitized by cyclic nigerosylnigerose-based nanosponges crosslinked by pyromellitate1. Issue 10 (14th March 2015) - Wei, Xueqin; Liang, Wenting; Wu, Wanhua; Yang, Cheng; Trotta, Francesco; Caldera, Fabrizio; Mele, Andrea; Nishimoto, Tomoyuki; Inoue, Yoshihisa
<x xml:space="preserve">Abstract</x> The enantioselectivity of the (E)-cyclooctene produced critically depended on the solvent and also on the phase evolved, maximizing at the flowing/rigid gel border.